Improved in vitro rooting and acclimatization of “Violetta” Artichoke and “Green Globe” Artichoke - Khai, Hoang Dac; Mai, Nguyen Thi Nhu; Anh, Hoang Le Lan; Nguyet, Nguyen Nhu Minh; Long, Ho Viet; Luan, Vu Quoc; Hien, Vu Thi; Tung, Hoang Thanh; Cuong, Do Manh; Lich, Tran Van; et al. (Vietnam Journal of Biotechnology, 2021)
Artichoke (Cynara scolymus L.), a medicinal plant with high economic value, contains high levels of phenolic compounds; especially cynarine, which plays an important role in preventing cancer, cardiovascular disease, osteoporosis, diabetes and neurodegeneration, etc. Currently, Artichoke micropropagation has achieved some success; however, the rooting efficiency and plantlet quality are still limited. In this study, improving the quality of Artichoke plantlet related to the shoot quality and suitable substrates in in vitro rooting stage was studied on “Violetta” Artichoke (VA) and “Green Globe” Artichoke (GA). The results showed that shoots (1.5 cm) cultured on MS medium supplemented 0.5 mg/L KIN were most suitable to shoot multiplication of VA with the number of shoots/explant (3.67 shoots), number of shoots ≥ 2 cm (3 shoots); while, 1.0 mg/L BA was suitable to shoot multiplication of GA (5.33 shoots; 5.00 shoots; respectively) after 4 weeks of culture. Besides, the in vitro rooting was improved using 8 g/L commercial agar for VA; meanwwhile, 3 g/L gelrite for GA. In addition, the nylon bag culture system (120 mm × 250 mm) has potential in plantlet production (15 plants/bag) and can be applied for large scale micropropagation. In addition, VA and GA plantlets derived from in vitro culture gave the good acclimatization, growth and development after 8, 12 and 20 weeks cultivating at the green house conditions.